Bundle Prevention Form Filling Completeness of Surgical Site Infection (SSI) on Sectio Caesarea Patients in 2016 - Adita Puspitasari Swastya Putri; Kurnia Dwi Artanti; Dwiono Mudjianto (Jurnal Berkala Epidemiologi, 2017)
Hospital Acquired Infections (HAIs) are infections obtained by patients during treatment procedures and medical procedures in health care facilities in the range of ≥ 48 hours to ≤30 days and infections are observed after patients leave the health care facility. One of the HAIs that often happens is Surgical Site Infection (SSI) so surveillance is needed. This study aims to look at the description of the presence, filling, and completeness of SSI prevention bundles in sectio-caesarea patients at X Surabaya Hospital. This research is a descriptive study with a cross-sectional study design with a total sample of 47 patients taken by simple random sampling in sectio caesarea patients at Hospital X Surabaya in January - June 2016. Primary data collection using interview techniques, while secondary data using a study of the results of the recapitulation Committee of The Infection Prevention and Control Program and the SSI prevention bundle. Data analysis was performed descriptively and presented in graphical form with narration. The results showed that the majority of the patient's medical record status was not accompanied by the SSI prevention bundle with filling and completeness of data that was still below the prescribed standard (64%). Although the implementation of SSI surveillance is in accordance with the guidelines for infection surveillance, there are still some shortcomings in terms of data accuracy, so the information obtained is still not well reported.